(untitled) (Research, Society and Development, 2022)
This study aimed to investigate the kinematic effects of dynamic mobilization exercises on the axial segment in horses. Twelve horses crossbreed were used, which were monitored before (day 0) and at the end of the experimental period (day 120), distributed in an entirely randomized design, totalizing six repetitions per treatment The treatments consisted of two experimental groups, one composed of horses not performing the dynamic mobilization exercises and the other composed of horses submitted to the mobilization program. The static kinematic variables were evaluated, by means of hemispherical markers such as depth (cm), angle (°), difference in depth and angle, for each vertebral level analyzed (T10, T13, T17, L1 and L3), as well as total range of motion for depth and angle, in which this parameter expressed the thoracolumbar motion in its entirety. The performance of dynamic mobilization produced a significant (P<0.05) decrease in thoracolumbar depth and increase in thoracolumbar flexion angle, compared to the group that did not perform the functional exercises. A reduction in the total thoracolumbar depth of -6.28 cm (P<0.0001) was observed in horses that underwent the exercises. The same response behavior was verified for angular measurement, in which there was an increase in the total ROM of the angle, reflecting thoracolumbar flexion, of 15.54°(P<0.00001). It was concluded that dynamic mobilization exercises consistently produce flexion of the axial segment, becoming a potential tool to improve range of motion and thoracolumbar function in horses.